Relative orientation with limited control in close range Photogrammetry - Rüther, Heinz (School of Architecture, Planning and Geomatics, 2016)
In close-range photogrammetry, situations can arise in which it is difficult or impossible to establish a network of control points as required for a conventional absolute orientation procedure. The thesis investigates the replacement of the traditional control network by a few control distances measured between well-defined artificial markers or natural feature points. The measured distances must then serve to reduce deformations suffered by the photogrammetric model in the orientation procedures. All investigations are based on analytical rather than analogue photogrammetry. After a review of the concepts of rotation matrices, least squares adjustment and the generation of synthetic image co-ordinate observations, the study is executed in three major steps. A test field of high precision is established by means of space intersection and a camera calibration method for close-range cameras is developed which combines perspective projection with geodetic observations of the lens system parameters. Thus a problem inherent in many camera calibration methods, namely the exact determination of the perspective centre, is largely overcome. Deformation characteristics related to error in elements of interior and relative orientation are determined by the controlled introduction of errors into these elements. The deformations are presented in tabular and diagrammatical form. An analysis of the deformation leads to the conclusions of theoretical and practical relevance for close-range photogrammetry. As a result of the deformation analysis mathematical models are introduced which utilise the measured distances for the reduction of model deformations. The efficiency of homogeneous scaling, affine scaling and convergency correction, as applied individually and in various combinations, is tested. A mathematical formulation of the converging correction as a restraining condition in a least squares adjustment is developed for this purpose. It is shown that a convergency error is less relevant to close-range photogrammetry than generally assumed and that characteristic model deformations in close-range photogrammetry have the character of affine scale errors. Throughout the thesis algorithms are developed which make it possible to execute all computations on computers with limited memory capacity. A program sample for the relative orientation adjustment is given in Appendix IV to demonstrate the memory saving techniques. Finally the results of the investigation are applied to the survey of shoulder height of African elephants in their natural habitat. Equipment and field work are described and results reported.